Equatorial guinea : Staff Report for the 2005 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2005)
This 2005 Article IV Consultation highlights that monetary development in the Republic of Equatorial Guinea continues to be dominated by fiscal policy. Fiscal outcome was marked by an increase in the fiscal surplus in 2004 compared with 2003 on account of a stronger-than-expected revenue performance owing to higher oil prices and increase in hydrocarbon production that was partly offset by a substantial increase in capital expenditure. Important progress has also been made with regard to transparency and accountability of oil-related revenues and public finance.